Economic development of a peripheral region: the case of Karelian timber industry - Pavel Druzhinin (European Regional Science Association (ERSA), 2003)
This paper focuses on current patterns of restructuring in Russian Karelia's timber industry, which constitutes the backbone of the regional economy. In particular, the paper investigates the relationship between an increased export orientation of this industry and a notable worsening of its output structure, combined with a lack of technological innovations. This situation results in a general instability of Karelian economy, which is increasingly dependent on fluctuations of international timber prices, as well as on exchange rate policy of the Russian government and central bank. This results in a decline in Karelian living standards, especially in remote rural settlements, which are crucially dependent on export of raw timber. Moreover, the current business climate in Russia strengthens Karelia's specialisation in export of raw timber and deters investment in higher-added-value timber-processing industries. The paper discusses this relationship and suggests that the Republic should start to stimulate the development of domestic-market-oriented timber-processing industries on account of an active inward investment promotion strategy.
Keywords: 330